2003
DOI: 10.11646/zootaxa.371.1.1
|View full text |Cite
|
Sign up to set email alerts
|

South African Latrunculiidae (Porifera: Demospongiae: Poecilosclerida): descriptions of new species of Latrunculia du Bocage, Strongylodesma Lévi, and Tsitsikamma Samaai & Kelly

Abstract: A recent major revision of the Family Latrunculiidae (Demospongiae: Poecilosclerida) recognised four valid genera; Latrunculia du Bocage, Sceptrella Schmidt, Strongylodesma Lévi, and Tsitsikamma Samaai & Kelly, from South Africa. The major diagnostic characters of the Family Latrunculiidae are the possession of discate acanthose microrhabd microscleres called acanthodiscorhabds, or more traditionally, “chessman” spicules, that form a dense palisade in the outer ectosome, a tangential layer of styles or ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(65 citation statements)
references
References 6 publications
2
63
0
Order By: Relevance
“…Species of Strongylodesma have strongyles as megascleres with a distinctive paratangential ectosomal layer, the thickness of this layer differing considerably between species, most of which have very thick layers. In Strongylodesma the ectosomal strongyles tend to be arranged peripherally perpendicular to the surface; this arrangement is assumed to be homologous to that of the erect layer of anisodiscorhabds of Latrunculia (Samaai & Kelly, 2002;Samaai et al, 2003Samaai et al, , 2004. Strongylodesma areolata differs from S. algoaensis, S. tsitsikammaensis and S. aliwaliensis by the smaller size of the megascleres ((299 (282-319) Â 6 (5 -7) um in the holotype MNHN VEM 131-DCL 1425)), and in the possession of terminally spined strongyles (as opposed to smooth strongyles in the South African species) (see Table 1).…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Species of Strongylodesma have strongyles as megascleres with a distinctive paratangential ectosomal layer, the thickness of this layer differing considerably between species, most of which have very thick layers. In Strongylodesma the ectosomal strongyles tend to be arranged peripherally perpendicular to the surface; this arrangement is assumed to be homologous to that of the erect layer of anisodiscorhabds of Latrunculia (Samaai & Kelly, 2002;Samaai et al, 2003Samaai et al, , 2004. Strongylodesma areolata differs from S. algoaensis, S. tsitsikammaensis and S. aliwaliensis by the smaller size of the megascleres ((299 (282-319) Â 6 (5 -7) um in the holotype MNHN VEM 131-DCL 1425)), and in the possession of terminally spined strongyles (as opposed to smooth strongyles in the South African species) (see Table 1).…”
Section: Remarksmentioning
confidence: 99%
“…The sponge was found in a moderately rugged rocky bottom habitat, with patches of sand between these rocks, together with coral and other sponges, at a depth of 15 m. Strongylodesma algoaensis differs from the genus holotype of the type species S. areolata Lévi by the larger size of the megascleres ((328 (307 -355) Â 9 (7 -9) um (see Table 1)), and in the possession of smooth strongyles (as opposed to faintly terminally spined strongyles in the holotype). This species is known so far only from the description of Samaai et al (2003) and is one of three species described from South Africa. It is closest to S. tsitsikammaensis (Samaai et al, 2003), from which it differs in habitat, the latter found in intertidal rock pools and gullies and the former restricted to deeper waters on rocky platforms.…”
Section: Remarksmentioning
confidence: 99%
“…The genus Tsitsikamma is endemic to South Africa. 13 The identification of sponges belonging to this family was predominantly based on a number of key morphological features, including, in most genera, the presence of the characteristic silica-based discorhabd microscleres which differ structurally between the different genera ( Figure 3).…”
Section: Biodiversity Of South African Latrunculid Spongesmentioning
confidence: 99%
“…However, the genus Strongylodesma is an enigma within the family Latrunculiidae, because species within this genus do not contain these distinctive discorhabd microscleres. 13 Shortly after this taxonomic revision was published, the family Latrunculiidae was further expanded to include another new endemic South African genus, Cyclacanthia, which incorporated three new species collected from the Agulhas ecoregion (C. bellae, C. cloverlyae and C. mzimayensis). 14 The type specimen for this genus, C. bellae, described from Algoa Bay, was originally misidentified as L. bellae (Samaai and Kelly, 2003) and placed in the genus Latrunculia.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation